Atomic Layer Deposition Assisted Encapsulation of Quantum Dot Luminescent Microspheres toward Display Applications. Issue 12 (24th April 2020) - Fang, Fan; Liu, Mengjia; Chen, Wei; Yang, Hongcheng; Liu, Yizun; Li, Xiang; Hao, Junjie; Xu, Bing; Wu, Dan; Cao, Kun; Lei, Wei; Müller‐Buschbaum, Peter; et al.
Abstract: Quantum dots (QDs) are promising for being used in advanced displays due to their outstanding emission properties. Herein, a novel encapsulation method for QDs is reported and ultra‐stable QDs@SiO2 @Al2 O3 luminescent microspheres (QLuMiS) are obtained by combining a sol–gel method for the intermediate SiO2 layer with a fluidized powder atomic layer deposition (ALD) for the outer Al2 O3 layer. The rich hydroxyl coverage on the QDs@SiO2 surface provides abundant chemisorption sites, which are beneficial for the deposition of Al2 O3 in the ALD process. Simultaneously, the water‐oxygen channels in the SiO2 layer are blocked by the Al2 O3 layer, which protects the QDs against deterioration. Consequently, the QLuMiS exhibit an excellent stability with 86% of the initial light conversion efficiency after 1000 h of blue light aging under a light power density of 2000 mW cm −2 . Such stability is significantly better than that of QDs@Al2 O3 and QDs@SiO2 samples. Moreover, under this strong irradiation aging condition with blue light, the extrapolated lifetime (L50) of QLuMiS is 4969 h, which is ten times longer than that of QDs@SiO2 and is the best record as far as is known. Finally, a prototype of a QLuMiS‐based cellphone screen with a wide color gamut of 115% NTSC is demonstrated. Abstract : Ultra‐stable QDs@SiO2 @Al2 O3 luminescent microspheres (QLuMiS) are prepared by combining the sol‐gel method with the powder fluidized atomic layer deposition technique. The intermediate silica layer can provide favorable conditions for the deposition of alumina with excellent barrier properties. The L50 lifetime of QLuMiS reaches up to 4969 h under irradiation of blue light with light power density of 2000 mW cm −2 .